THE EFFECT OF RELATED-PARTY TRANSACTION, PROFITABILITY, LEVERAGE, AND EXECUTIVE EQUITY INCENTIVES ON THE OCCURRENCE OF ACCOUNTING IRREGULARITIES (AN EMPIRICAL STUDY ON NON-FINANCIAL COMPANIES LISTED ON IDX YEAR 2012-2014) - Ashdiqa, Cut Chaira; Fahlevi, Heru; Afrianandra, Cut (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
The purpose of this study is to examine the determinants of accounting irregularities from its management, financial activities, and conditions. Based on fraud triangle theory and agency theory, variables related party transaction, profitability, leverage, and executive equity incentives are hypothesized to affect the occurrence of accounting irregularities. The occurrence of accounting irregularities was measured using dummy variable based on the incidence of financial restatement which resulted from either error or fraud. By using purposive sampling method, this study has drawn sample of 46 companies and 46 matched-pairs from total non-financial companies listed in IDX year 2012-2014. The hypothesis testing is done through binary logistic regression. The result of this study shows that, related party transaction which was measured by the percentage of receivables with related partiesand profitability which was measured by ROA, have a significant positive impact on the occurrence of accounting irregularities. On the other hand, variable leverage measured by debt-to-equity and executive equity incentives measured by managerial ownership arenot significantly affectthe occurrence of accounting irregularities.